Oxidative acetylenic coupling reactions as a surface chemistry tool - Ciampi, S.; James, M.; Darwish, Nadim; Luais, E.; Guan, B.; Harper, J.; Gooding, J. (R S C Publications, 2011)
A novel method to prepare redox monolayers on silicon electrodes has been developed that employs CuI-catalyzed oxidative acetylenic coupling reactions for molecular electronic type applications. As the first case study, ethynylferrocene was covalently immobilized onto an acetylene-terminated monolayer on a Si(100) surface to give a 1,3-diyne (CC-CC-) linked redox assembly. The derivatization process requires no protection/de-protection steps, nor activation procedures. The effect of the conjugated diyne linkage on the rate of electron transfer between tethered ferrocenyl units and the silicon electrode is benchmarked against well-established "click" products (i.e. 1,2,3-triazole linkage). The surfaces, after each step, are characterized thoroughly using X-ray reflectivity (XRR), X-ray photoelectron spectroscopy (XPS), electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The coupling chemistry provides a useful strategy for functionalizing silicon surfaces and contributes to an expanding repertoire of wet chemistry routes for the functionalization of solid substrates.